Evaluasi Manajemen Insiden Layanan TI pada Aplikasi E-Wallet Menggunakan Cobit 5 DSS02 : Studi Kasus: Ovo - Abdillah Zahid; Syarifah Rizqiyah; Nesa Herlika Balqis; Eriene Dheanda Absharina (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The rapid development of financial technology has driven the increased use of digital wallets, such as OVO, in daily transactions. This growing dependence on digital services requires stable and well-structured information technology service management, particularly in incident handling. Disruptions such as transaction failures, notification delays, incorrect balance deductions, and system errors can significantly affect user satisfaction and trust. This study aims to evaluate the information technology service incident management of the OVO application using the COBIT 5 framework, specifically the DSS02 domain (Manage Service Requests and Incidents). This research employed a qualitative descriptive approach through literature review and direct observation of the application. The evaluation results indicate that most DSS02 practices have been formally implemented and documented, including incident recording, classification, investigation, and resolution. Based on the COBIT 5 capability level mapping, the IT service incident management of the OVO application is at Level 3 (Defined Process). This level shows that the processes have been standardized and consistently executed; however, they have not been fully measured and quantitatively controlled. Therefore, improvements are needed in performance monitoring, Service Level Agreement (SLA) transparency, and continuous evaluation to achieve a higher maturity level and enhance service quality.